Recommendations to Synthetize Old and New β-Lactamases Inhibitors: A Review to Encourage Further Production - Silvana Alfei; Guendalina Zuccari (MDPI AG, 2022)
The increasing emergence of bacteria producing β-lactamases enzymes (BLEs), able to inactivate the available β-lactam antibiotics (BLAs), causing the hydrolytic opening of their β-lactam ring, is one of the global major warnings. According to Ambler classification, BLEs are grouped in serine-BLEs (SBLEs) of class A, C, and D, and metal-BLEs (MBLEs) of class B. A current strategy to restore no longer functioning BLAs consists of associating them to β-lactamase enzymes inhibitors (BLEsIs), which, interacting with BLEs, prevent them hydrolyzing to the associated antibiotic. Worryingly, the inhibitors that are clinically approved are very few and inhibit only most of class A and C SBLEs, leaving several class D and all MBLEs of class B untouched. Numerous non-clinically approved new molecules are in development, which have shown broad and ultra-broad spectrum of action, some of them also being active on the New Delhi metal-β-lactamase-1 (NDM-1), which can hydrolyze all available BLAs except for aztreonam. To not duplicate the existing review concerning this topic, we have herein examined BLEsIs by a chemistry approach. To this end, we have reviewed both the long-established synthesis adopted to prepare the old BLEsIs, those proposed to achieve the BLEsIs that are newly approved, and those recently reported to prepare the most relevant molecules yet in development, which have shown high potency, providing for each synthesis the related reaction scheme.